2012
DOI: 10.1111/j.1467-985x.2012.01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Assortative Mating and Divorce: Evidence from Austrian Register Data

Abstract: We show that changes in assortative mating patterns along the dimensions of age, ethnicity, religion and education are not responsible for the increasing marital instability over the last four decades in Austria. Without the rise in the age at marriage, divorce rates would be considerably higher. Immigration and secularization, and the resulting supply of spouses with diverse ethnicity and religious denominations had no overall eect on divorce rates. Countervailing eects in line with theoretical predictions os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
18
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 50 publications
7
18
0
1
Order By: Relevance
“…As an illustration, Weiss and Willis (1997) found evidence that couples with similar levels of schooling are more likely to marry and less likely to divorce. Likewise, similarities in terms of age, region of origin, ethnicity, religion, and social background, have been found to be associated with longer durations of marriages (see Frimmel et al, 2009 for a review), an observation that is confirmed in our surveys (see Section 5.3).…”
Section: Assortative Matingsupporting
confidence: 82%
“…As an illustration, Weiss and Willis (1997) found evidence that couples with similar levels of schooling are more likely to marry and less likely to divorce. Likewise, similarities in terms of age, region of origin, ethnicity, religion, and social background, have been found to be associated with longer durations of marriages (see Frimmel et al, 2009 for a review), an observation that is confirmed in our surveys (see Section 5.3).…”
Section: Assortative Matingsupporting
confidence: 82%
“…As an illustration, Weiss and Willis (1997) find evidence that couples with similar level of schooling are more likely to marry and less likely to divorce. Likewise, similarity in terms of age, region of origin, ethnicity, religion, and social background have been found to be associated with longer durations of marriages (see Frimmel et al 2009, for a survey), an observation that is confirmed in our surveys (see section 5.1).…”
Section: Assortative Matingsupporting
confidence: 72%
“…9 Finally, I estimate the model on the sample of single-headed households to test for spurious effects of unilateral divorce laws on time spent in leisure, as well as household work and market work. While single-headed households may be affected by unilateral divorce through selection into marriage, if we see similar effects of 9 Since Rotz (2012) and Frimmel et al (2013) show wife's age at marriage to be the primary predictor of the decrease in the divorce rate, wife's age at marriage could be used as an alternative variable to subset the sample into high-risk groups. However, the limited variation in wife's age at marriage among our sample limit the usefulness of this method here.…”
Section: Data and Empirical Strategymentioning
confidence: 99%